The Influence of Work Competence and Employee Engagement on Employee Performance with Organizational Culture as a Moderating Variable - Albert Sinansari; Habib Hakim; M. Tahir (International Journal of Science and Environment (IJSE), 2026)
Purpose: This study examines the influence of job competence and employee engagement on employee performance at Yayasan Medan Mulia/Mian Zhong, Medan, with organizational culture as an intervening variable in the SEM-PLS model. Research Methodology: A quantitative explanatory design was applied using a census technique involving all 127 foundation employees from elementary, junior high, and senior high school units, including teachers, security officers, janitors, administrative staff, and educational personnel. Primary data were collected through Likert-scale questionnaires and analyzed using SEM-PLS by evaluating the measurement model, discriminant validity, collinearity, model fit, coefficient of determination, effect size, and bootstrapping-based hypothesis testing. Results: The measurement model met validity and reliability criteria, as outer loadings exceeded the recommended threshold, Cronbach’s alpha ranged from 0.901 to 0.936, composite reliability ranged from 0.918 to 0.946, and AVE ranged from 0.693 to 0.770. HTMT, Fornell-Larcker, and inner VIF results also indicated acceptable discriminant validity and no multicollinearity. However, the structural model showed weak explanatory power, with R-squared values of 0.032 for employee performance and 0.007 for organizational culture. All direct and indirect hypotheses were rejected because their p-values exceeded 0.05. Conclusions: Job competence, employee engagement, and organizational culture were not dominant predictors of employee performance in this foundation context. Limitations: The study was limited to one educational foundation and used heterogeneous job categories. Contributions: This study contributes empirical evidence that employee performance in educational foundations may require broader explanatory variables beyond competence, engagement, and organizational culture, particularly leadership, motivation, compensation, work environment, and performance appraisal systems.